Too much to process? Exploring the relationships between communication and information overload and videoconference fatigue. - Benjamin J Li; Heng Zhang; Christian Montag (PLoS ONE)
The adoption of videoconferencing has brought significant convenience to people's lives. However, as videoconferencing usage has skyrocketed, it has unveiled a range of side effects, most notably videoconference fatigue (VF). In response, this paper employed the Limited Capacity Model of Motivated Mediated Message Processing (LC4MP) as a theoretical framework to conduct two comprehensive investigations, centering on the impact of verbal communication overload on users' information overload and VF. We conducted two studies to test our propositions and conceptual model. Study One focused on the educational context and comprised a survey with 489 students. In Study Two, we expanded our exploration to the professional use of videoconferencing in two populations: Singapore and Germany. A total of 610 responses were collected in Singapore, with the German sample constituting a total of 948 participants. Results from both studies consistently demonstrated a positive relationship between videoconference frequency and communication overload. Additionally, perceived communication overload was positively associated with information overload and VF. Based on the findings of the two studies, we discuss the theoretical and practical implications and suggest new directions for videoconferencing research.